FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN CONGESTIVE HEART FAILURE DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Fifi Oktaviani; Safri Safri; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Congestive Heart Failure is inability of the heart to pump blood to meet the needs of oxygen andnutriens to the body tissues. This study aims to determine the factors related to mediactionadherence compliance in patients Congestive Heart Failure. This Study used descriptivecorrelation design with cross sectional approach. Sample of this study were 20 respondents usingpurposive sampling technique. This study measured by quetionnaire. Data analysis used wereunivariate and bivariate with chi-square. The results of this study that factors related to medicationadherence in patients CHF is the distance to the treatment site with p value 0, 015 (p < 0,05),family support with 0, 015 (p < 0,05), knowledge with p value 0, 017 (p < 0,05). Factor unrelatedto medication adherence compliance in patients CHF is age with p value 0, 828 (p > 0,05),education with p value 0, 644 (p > 0,05), socioeconomic status with p value 0, 613 (p > 0,05), andperception with dengan p value 0, 051 (p < 0,05). The result of this study was recommend thathealth service to give information in medication adherence and prevent recurrence due toincompliance to take medication in patient congestive heart failure.Keyword: Congestive Heart Failure, Medication Adherence